Source unreliability decreases but does not cancel the impact of social information on metacognitive evaluations - JACQUOT, Amelie; ESKENAZI, Terry; SALES-WUILLEMIN, Edith; MONTALAN, Benoit; PROUST, Joelle; GREZES, Julie; CONTY, Laurence (Frontiers in Psychology, 2015)
Through metacognitive evaluations, individuals assess their own cognitive operations with respect to their current goals. We have previously shown that non-verbal social cues spontaneously influence these evaluations, even when the cues are unreliable. Here, we explore whether a belief about the reliability of the source can modulate this form of social impact. Participants performed a two-alternative forced choice task that varied in difficulty. The task was followed by a video of a person who was presented as being either competent or incompetent at performing the task. That person provided random feedback to the participant through facial expressions indicating agreement, disagreement or uncertainty. Participants then provided a metacognitive evaluation by rating their confidence in their answer. Results revealed that participants’ confidence was higher following agreements. Interestingly, this effect was merely reduced but not canceled for the incompetent individual, even though participants were able to perceive the individual’s incompetence. Moreover, perceived agreement induced zygomaticus activity, but only when the feedback was provided for difficult trials by the competent individual. This last result strongly suggests that people implicitly appraise the relevance of social feedback with respect to their current goal. Together, our findings suggest that people always integrate social agreement into their metacognitive evaluations, even when epistemic vigilance mechanisms alert them to the risk of being misinformed.